2021
DOI: 10.3390/ma14123439
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Porcine Xenograft over Autograft in Sinus Lift: A Randomised Clinical Trial

Abstract: This study aimed to compare the performance of intra-oral autologous bone grafts versus porcine xenografts in a two-step lateral window sinus lift. This split-mouth randomised controlled trial sequentially enrolled 12 patients with a 6-month follow-up. For each patient, a simultaneous randomised bilateral maxillary sinus lift was performed and filled with autologous bone from the mandible (control) or a porcine xenograft (test). A bone biopsy sample was collected during the implant placement for histological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…Several treatment options have been utilized to overcome the issue of inadequate bone volume in the lateral area of the maxilla [ 17 ]. The subantral residual alveolar bone plays a significant role with respect to the most convenient option of surgical procedure and the timing of implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…Several treatment options have been utilized to overcome the issue of inadequate bone volume in the lateral area of the maxilla [ 17 ]. The subantral residual alveolar bone plays a significant role with respect to the most convenient option of surgical procedure and the timing of implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence showed that MSFA predictably leads to high implant survival rates, limited peri-implant marginal bone loss, and resulted in few overall surgical and prosthetic complications in maxillary patients [ 3 , 4 , 5 , 6 , 7 , 8 ]. The lateral osteotomy technique to approach the MFSA for increasing bone volume in the posterior maxilla is a well-established and documented surgical procedure allowing for implant placement [ 3 , 13 , 14 , 31 ]. Irrespective of the grafting materials applied (i.e., autogenous bone, allografts, xenografts, alloplastic), MFSA is accompanied by increased implant stabilization and new bone formation [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lateral osteotomy technique to approach the MFSA for increasing bone volume in the posterior maxilla is a well-established and documented surgical procedure allowing for implant placement [ 3 , 13 , 14 , 31 ]. Irrespective of the grafting materials applied (i.e., autogenous bone, allografts, xenografts, alloplastic), MFSA is accompanied by increased implant stabilization and new bone formation [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations